Child Maltreatment Among U.S. Air Force Parents Deployed in Support of Operation Iraqi Freedom/Operation Enduring Freedom. (February 2015) - Rabenhorst, Mandy M.; McCarthy, Randy J.; Thomsen, Cynthia J.; Milner, Joel S.; Travis, Wendy J.; Colasanti, Marie P.
This study examined child maltreatment perpetration among 99, 697 active-duty U.S. Air Force parents who completed a combat deployment. Using the deploying parent as the unit of analysis, we analyzed whether child maltreatment rates increased postdeployement relative to predeployment. These analyses extend previous research that used aggregate data and extend our previous work that used data from the same period but used the victim as the unit of analysis and included only deploying parents who engaged in child maltreatment. In this study, 2% ( n = 1, 746) of deploying parents perpetrated child maltreatment during the study period. Although no overall differences were found in child maltreatment rates postdeployment compared to predeployment, several maltreatment-related characteristics qualified this finding. Rates for emotional abuse and mild maltreatment were lower following deployment, whereas child maltreatment rates for severe maltreatment were higher following deployment. The finding that rates of severe child maltreatment, including incidents involving alcohol use, were higher postdeployment suggests a need for additional support services for parents following their return from combat deployment, with a focus on returning parents who have an alcohol use problem.